Morfología y vulnerabilidad costera por erosión en el litoral de Campeche, México - Castro Soriano, Bianca Stephanya (Universidad Autónoma Metropolitana, 2015)
During the dry season, rain and norths 2013 and 2014 topographic surveys were performed in 15 beaches on the coast of Campeche, Mexico, a morphological analysis was developed in order to determine the present deposit-erosion and an analysis coast of different years 2004, 2011 and 2013 satellite images to identify areas of erosion or accumulation and erosion rates. Sediment samples were collected to analyze the energy conditions of the environment and the origin of sediments by grain size and mineral composition analysis. An analysis of empirical orthogonal functions was performed to know the different modes of variation along the coast. With geological / morphological and physical / hydrodynamic data obtained coastal vulnerability index was calculated. In addition, a survey was conducted to 200 people from the public opinion in the coastal area, to meet the social perception of the phenomena of erosion, climate change, risk and preventive measures. The results showed that on the coast of Campeche two geological processes dominate: continuous erosion and erosion-deposit fluctuation. With the study of empirical orthogonal functions two modes of variation were determined: Profile of ”Storm.and profile ”Normal”. Furthermore two types of sediment were identified: of Transition (terrigenous material and / or limestone) were dominate biogenic thinly sands and coarse sands composed of limestone eroded bodies. Sites with very high vulnerability are found in the Isla del Carmen: Playa Norte, Bahamita, CASES and San Nicolasito; high on sites that are associated with the outputs of the Lagoonal bottom, Sabancuy and Puente Dos Bocas: medium for those with long stretch beaches of Isla Aguada, KM 45, Villa Quietud, Chenkan and Punta Chen; and finally to those with low natural protection in infrashore such as rock beach Puerto Real. The 80 % of respondents believe that the coast is paramount, but only about 13 % knows about the problem of coastal erosion, furthermore 90 % ignores the existence of the Municipal Risk Atlas to face hydro meteorological risks. Erosion is being generated mainly by hydro meteorological 3 conditions of each era, and secondarily by coastal protection infrastructure (breakwaters, jetties, tetrapods). Critical erosion sites are North Beach, Beach Club, CASES, KM 45. Mitigation measures are necessary for each of the sites, but must be established with proper study and modeling to determine whether coastal protection infrastructure would have a benefit to the portion of the coast.; Durante la temporada de secas, lluvias y nortes del 2013 y 2014 se realizaron levantamientos topográficos en 15 playas del litoral de Campeche, México, se elaboró un análisis morfológico con el fin de determinar los procesos de erosión-deposito presentes y un análisis de línea de costa de diferentes años 2004, 2011 y 2013 con imágenes de satélite para definir las ´áreas de erosión o acumulación y tasas de erosión. Se colectaron muestras de sedimentos para analizar las condiciones energéticas del ambiente y la procedencia de los sedimentos a través de análisis granulométricos y de composición mineral. Se realizó un análisis de funciones empíricas ortogonales para conocer los distintos modos de variación a lo largo del litoral. Con los datos geológicos/morfológicos y físicos/hidrodinámicos obtenidos se calculó el ´índice de vulnerabilidad costera. Además, se realizó una encuesta a 200 personas de la opinión pública de la zona litoral, para conocer la percepción social de los fenómenos de erosión, cambio climático, riesgo y de medidas preventivas. Los resultados mostraron que en el litoral de Campeche dominan dos procesos geológicos: erosión continua y fluctuación erosión-depósito. Con el estudio de las funciones empíricas ortogonales se determinaron dos modos de variación: perfil de “Tormenta” y perfil “Normal”. Así mismo se identificaron dos tipos de sedimentos: de transición (material terrígeno y/o calcáreo) en los que dominan arenas finas y piogénicos constituido por arenas gruesas compuestas por restos calcáreos de organismos erosionados. Los sitios con vulnerabilidad muy alta se encuentran en la Isla del Carmen: Playa Norte, Bahamita, CASES y San Nicolasito; alta en los sitios que están asociados a las salidas de las Bocas: Las Bombas, Sabancuy y Puente Dos Bocas: media para los que presentan playas de larga extensión Isla Aguada, KM 45, Villa Quietud, Chenkan y Punta Chen; y finalmente baja para aquellos que presentan protección natural en la infraplaya como es el beach rock Puerto Real. El 80 % de los encuestados consideran que el litoral es de suma importancia, pero solo cerca del 13 % entiende la problemática de la 1 erosión costera, así mismo el 90 % ignora la existencia del Atlas de Riesgo Municipal, para hacer frente a los riesgos hidrometereológicos. La erosión está siendo generada principalmente por condiciones hidrometereológicas de cada ´época, y secundariamente por las infraestructuras costeras de protección (escolleras, espigones, tetrápodos). Los sitios críticos de erosión son Playa Norte, Club de Playa, CASES, Km 45. Las medidas de mitigación son necesarias para cada uno de los sitios, pero deben de establecerse con el estudio y modelado adecuado para definir si las infraestructuras costeras de protección tendrían un beneficio hacia la porción del litoral.